Достатність доказів у кримінальному провадженні - Зінченко, Валерій Михайлович; Зинченко, Валерий Михайлович; Zinchenko, Valeriy M. (My University, 2020)
Дисертація на здобуття наукового ступеня кандидата юридичних наук за спеціальністю 12.00.09 – кримінальний процес та криміналістика; судова експертиза; оперативно-розшукова діяльність. – Національний університет «Одеська юридична академія», Одеса, 2020. Дисертація є першою в Україні, після набрання чинності КПК України 2012 року, кваліфікаційною науковою працею, в якій на основі комплексного аналізу проблем правотворчого та правозастосовного характеру розроблено й обґрунтовано концепцію достатності доказів у кримінальному провадженні. У дисертації охарактеризовано систему процесуальних властивостей доказів, розкрито їх зміст і встановлено місце у ній достатності доказів. Розкрито сутність достатності доказів як їх процесуальної властивості, на підставі чого надано авторське визначення її поняття і запропоновано авторську концепцію достатності доказів у кримінальному провадженні. Визначено співвідношення достатності доказів та предмета і меж кримінального процесуального доказування. Встановлено взаємозв’язок достатності доказів і стандартів доказування у кримінальному провадженні. Розкрито механізм встановлення достатності доказів у ході застосування заходів забезпечення кримінального провадження. Визначено особливості встановлення достатності доказів у ході повідомлення про підозру. Охарактеризовано механізм встановлення достатності доказів у ході закінчення досудового розслідування. Розкрито особливості встановлення достатності доказів під час судового провадження у першій інстанції. Визначено механізм встановлення достатності доказів під час провадження у суді апеляційної інстанції. Розроблено науково обґрунтовані пропозиції, спрямовані на вдосконалення КПК України у частині визначення поняття достатності доказів і механізму її встановлення під час досудового розслідування та судового провадження.

Диссертация на соискание научной степени кандидата юридических наук по специальности 12.00.09 – уголовный процесс и криминалистика; судебная экспертиза; оперативно-розыскная деятельность. – Национальный университет «Одесская юридическая академия», Одесса, 2020. Диссертация является первой в Украине, после вступления в силу УПК Украины 2012 года, квалификационной научной работой, в которой на основе комплексного анализа проблем правотворческого и правоприменительного характера разработана и обоснована концепция достаточности доказательств в уголовном производстве. В диссертации охарактеризована система процессуальных свойств доказательств, раскрыто их содержание и установлено место в ней достаточности доказательств. Раскрыта сущность достаточности доказательств как их процессуального свойства, на основании чего предоставлено авторское определение ее понятия и предложена авторская концепция достаточности доказательств в уголовном производстве. Определено соотношение достаточности доказательств и предмета и пределов уголовного процессуального доказывания. Установлена взаимосвязь достаточности доказательств и стандартов доказывания в уголовном производстве. Раскрыт механизм установления достаточности доказательств в ходе применения мер обеспечения уголовного производства. Определены особенности установления достаточности доказательств в ходе сообщения о подозрении. Охарактеризован механизм установления достаточности доказательств в ходе окончания досудебного расследования. Раскрыты особенности установления достаточности доказательств во время судебного производства в первой инстанции. Определен механизм установления достаточности доказательств в ходе производства в суде апелляционной инстанции. Разработаны научно обоснованные предложения, направленные на совершенствование УПК Украины в части определения понятия достаточности доказательств и механизма ее установления в ходе досудебного расследования и судебного производства.

Dissertation for the scientific degree of the Candidate of Legal Sciences in specialty 12.00.09 – Criminal Procedure and Criminalistics; Forensic Examination; Operational search activity. – National University «Odesa Law Academy», Odesa, 2020. The dissertation is the first qualifying scientific work in Ukraine, after the entry into force the CPC of Ukraine from 2012, in which, on the basis of a complex analysis of problems of law-making and law enforcement nature, the concept of the sufficiency of evidences in criminal proceedings was developed and substantiated. The essence of the sufficiency of evidences is defined in the dissertation by the separation of its essential elements, which allowed to reveal the ontological bases of the concept of this procedural property of the evidences. The author defines of the notion of the sufficiency of evidences is provided as their systemic procedural property, which reflects the presence of a set of proper, admissible and reliable evidences and is established on the basis of the internal conviction of the subject of proof, which is based on a comprehensive, complete and impartial examination of all circumstances of the criminal proceedings at the specific moment of criminal proceedings for the purpose of making the appropriate procedural decision. The author’s conception of the sufficiency of evidences as their procedural property in criminal proceedings is offered. The system of procedural properties of evidences is characterized, in which, along with the sufficiency as their systemic procedural property, the relevance, admissibility and reliability as their individual procedural properties are distinguished. The relationship between the sufficiency of evidences and the subject of the criminal procedural proof is established. The relationship between the sufficiency of evidences and limits of the criminal procedural proof is established. The approaches to the definition of the concept and the system of standards of proof formed in the doctrine of the criminal process is investigated, on the basis of which the author’s approach to their definition is formed. The sufficiency of evidences is described as an indispensable condition for the application of standards of proof during adopting appropriate procedural decisions and ensuring of their observance, as well as the correlation of this property of evidences with each of the basic standards of formation of the level of conviction necessary for making the relevant procedural decision (standards «reasonable suspicion», «sufficient reason» and «beyond reasonable doubt») is revealed. The mechanism of establishing the sufficiency of evidences in the course of application of measures of ensuring criminal proceedings is revealed. Taking into account the rules of criminal procedural law, the jurisprudence of national courts and the ECHR and theoretical approaches, the peculiarities of establishing the sufficiency of evidences during the decision by the investigating judge on the issue of preventive measures are singled out. The peculiarities of establishing the sufficiency of evidences during the suspicion notification are identified. The doctrinal definition of the evidences sufficient for suspicion of committing a criminal offense is improved by presenting it taking into account the essential elements of the sufficiency of evidences with their specification regarding the notification of suspicion. The effect of the sufficiency of evidences on determining the form of the end of the pre-trial investigation is determined and it is considered as a necessary condition for ensuring the validity of the procedural decisions of the prosecution side to be taken in connection with the end of the pre-trial investigation. The peculiarities of establishing the sufficiency of evidences during trial at first instance are revealed. The content of the sufficiency of evidences in the context of the decree of a decision on the election, amendment and cancellation of measures of ensuring criminal proceedings as interim judgments and a guilty or acquittal verdict, a decision about the application of compulsory measures of medical or educational character, a decision about the close of criminal proceedings as final court decisions is characterized. The cases of evaluation of the evidences in terms of their sufficiency by the sides of the criminal proceedings during the trial at first instance are summarized. The mechanism for establishing the sufficiency of the evidences during the proceedings in the court of appeal is determined. The range of procedural documents and actions of the sides of the criminal proceedings, which reflect their assessment of the evidences in terms of their sufficiency during the appeal proceedings, are summarized. With a view to improve the regulatory model of the sufficiency of evidences as their procedural property, it is proposed to make changes and additions the CPC of Ukraine, which clarify the notion of the sufficiency of evidences by consolidating the notion of sufficient evidences, to clarify the range of circumstances to be taken into account by the investigating judge in deciding the issue of temporary restriction in the use of a special right and removal from office, to specify the grounds of the notice of suspicion and requirements for the contents of the suspicion report and the indictment etc.
дис. ... канд. юрид. наук: 12.00.09
Зінченко В.М. Достатність доказів у кримінальному провадженні: дис. ... канд. юрид. наук: 12.00.09 / Зінченко Валерій Михайлович. - Одеса, 2020. - 231 с.
Keywords: достатність доказів; процесуальні властивості доказів; оцінка доказів; досудове розслідування; судове провадження; достаточность доказательств; процессуальные свойства доказательств; оценка доказательств; досудебное расследование; судебное производство; sufficiency of evidences; procedural properties of evidences; evaluation of evidences; pre-trial investigation; court proceedings